Veryfied views on use of interleukin 2 and interleukins in treatment of advanced renal carcinoma - Żołnierek, Jakub; Wysocki, Piotr; Nurzyński, Paweł (Contemporary Oncology/Współczesna Onkologia, 2007)
Renal cell carcinoma is resistant to chemotherapy. To date vinblastin and 5-fluorouracil have been the most frequently used yet the objective response rate reaching 7% only slightly exceeds placebo effect or rate of spontaneous regression of the tumour. Hormone therapy failed to show any effect as well. In the past the only valuable method of treatment was immunotherapy. However, contemporary experience shows its effectiveness measured with objective response rate is about 15%. Moreover, there is no evidence to support its positive effect on overall survival of patients. It is far from satisfactory especially when toxicity and real costs of cytokine use are taken into account. The optimal regimen is still unknown. Although it has been proved that activity of IL-2 is related to its dose and dose intensity, then the effectiveness of subcutaneous IL-2 can be increased by its correlation with IFN-a or ex vivo activated cytotoxic lymphocytes, yet it is difficult to show evident benefit coming from such treatment because no data from randomized trials exist. Careful and exact enrolment based on known and recognized prognostic and predictive factors is the most important thing in immunotherapy. As new active and effective agents were developed indications for immunotherapy were restricted. But in future treatment paradigms for advanced renal cell cancer immunotherapy will still have its place as a valuable option.